Registration of 'Glee' Hard Red Spring Wheat. Issue 1 (9th November 2017) - Kidwell, K. K.; Pumphrey, M. O.; Kuehner, J. S.; Shelton, G. B.; DeMacon, V. L.; Rynearson, S.; Chen, X. M.; Guy, S. O.; Engle, D. A.; Baik, B.-K.; Morris, C. F.; Bosque-Pérez, N. A.
Abstract : Hard red spring wheat ( Triticum aestivum L.) is an important market class in the US Pacific Northwest, planted on an average of 44% of the spring wheat area in Washington State. The foliar fungal disease stripe rust (caused by Puccinia striiformis Westend. f. sp. tritici Eriks.) is a major problem for wheat cultivars grown in the region. The objective of this research was to develop an adapted hard red spring wheat cultivar with durable resistance to stripe rust. 'Glee' (Reg. No. CV‐1130, PI 666940) hard red spring wheat was developed by the Washington State University Agricultural Research Center and released in 2013 for production in the inland Pacific Northwest. Glee was derived from the cross WA7839/ID529 by a modified‐pedigree bulk‐breeding method. Glee was tested at sites across Washington under the designations WA8074 and Glee from 2009 to 2013. Glee is a medium‐early maturity, semidwarf cultivar broadly adapted to all spring wheat production areas of Washington, especially in areas that receive >400 mm average annual precipitation. Glee was released because of its combination of superior grain yield potential, a high level of adult‐plant resistance to stripe rust, and resistance to Hessian fly [ Mayetiola destructor (Say)]. Glee's grain protein concentration, grain volume weight, and milling and baking characteristics are comparable to other hard red spring wheat cultivars produced in the Pacific Northwest.